2013
DOI: 10.1021/am3022625
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature, High-Performance Solution-Processed Thin-Film Transistors with Peroxo-Zirconium Oxide Dielectric

Abstract: We demonstrated solution-processed thin film transistors on a peroxo-zirconium oxide (ZrO(2)) dielectric with a maximum temperature of 350 °C. The formation of ZrO(2) films was investigated by TG-DTA, FT-IR, and XPS analyses at various temperatures. We synthesized a zirconium oxide solution by adding hydrogen peroxide (H(2)O(2)). The H(2)O(2) forms peroxo groups in the ZrO(2) film producing a dense-amorphous phase and a smooth surface film. Because of these characteristics, the ZrO(2) film successfully blocked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(128 citation statements)
references
References 43 publications
10
115
2
Order By: Relevance
“…With increasing the annealing temperature, diffraction peak starts to show up at 500 1C, which is higher than the crystallization temperature observed by Chang [21]. This contains two peaks located at 2θ ¼ 30.41 and 50.61 corresponding to (111) and (220) reflections of cubic structure of ZrO 2 , which is in good agreement with the observation from Park [22] and Gurudayal [23]. When the annealing temperature rises up to 700 1C, the monoclinic phase of ZrO 2 appears as it is expected.…”
Section: Metal Insulator Semiconductor (Mis) Device Fabrication and Csupporting
confidence: 88%
“…With increasing the annealing temperature, diffraction peak starts to show up at 500 1C, which is higher than the crystallization temperature observed by Chang [21]. This contains two peaks located at 2θ ¼ 30.41 and 50.61 corresponding to (111) and (220) reflections of cubic structure of ZrO 2 , which is in good agreement with the observation from Park [22] and Gurudayal [23]. When the annealing temperature rises up to 700 1C, the monoclinic phase of ZrO 2 appears as it is expected.…”
Section: Metal Insulator Semiconductor (Mis) Device Fabrication and Csupporting
confidence: 88%
“…Although, different studies on the synthesis of peroxocomplexes [21,22] have been reported, studies on zirconium peroxocomplexes as the precursors for ZrO 2 or zirconium-based complex oxides are scarce. Gao et al [23] thin-film preparation, whereas Park et al [24] found some advantages of peroxo-mediated procedure for ZrO 2 films synthesis, as such as the homogeneous distribution on the substrate and high density of the film. High degree of homogeneity of the complex oxide is also found to be one of the advantages of peroxo-routes, as it allows lowering the temperatures of heat treatment while obtaining the desirable phase [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The breakdown voltage of the MIS capacitor can be appreciated at 36 V, which is due to the dielectric breakdown. The values of current density and capacitor breakdown voltage obtained are reliable for electronic device applications [25,26].…”
Section: Fully Solution-processed Transparent Mis Capacitorsmentioning
confidence: 72%